2016
DOI: 10.1016/j.nucengdes.2016.08.039
|View full text |Cite
|
Sign up to set email alerts
|

T-junction cross-flow mixing with thermally driven density stratification

Abstract: As a means of further elucidating turbulence-and stratification-driven thermal fatigue in the vicinity of T-junctions in nuclear power plants, a series of experiments have been conducted at the high temperature high pressure fluid-structure interaction T-junction facility of the University of Stuttgart with novel fluid measurement instrumentation. T-junction mixing with large fluid temperature gradients results in complex flow behavior, the result of density driven effects. Deionized water mixing at temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…As an extension of this tool development, the purpose of this study is to structure a thermal hydraulic database that contributes to core safety design to prevent core melting. In that respect, as mentioned above, J. Kickhofel et al [10] showed that temperature measurement by WMS technology can be applied under high pressure. On the other hand, the position of this study is to quantify the temperature distribution behavior of coolant in the fuel assembly (core) and to clarify the applicability of WMS technology.…”
Section: Purpose Of Sensor Developmentmentioning
confidence: 94%
See 4 more Smart Citations
“…As an extension of this tool development, the purpose of this study is to structure a thermal hydraulic database that contributes to core safety design to prevent core melting. In that respect, as mentioned above, J. Kickhofel et al [10] showed that temperature measurement by WMS technology can be applied under high pressure. On the other hand, the position of this study is to quantify the temperature distribution behavior of coolant in the fuel assembly (core) and to clarify the applicability of WMS technology.…”
Section: Purpose Of Sensor Developmentmentioning
confidence: 94%
“…The experimental pressure is the atmospheric pressure. It is desirable to evaluate in the atmospheric pressure region [10] where the relationship between the conductivity and the sensor signal becomes linear when evaluating the sensor in bundle.…”
Section: Purpose Of Sensor Developmentmentioning
confidence: 99%
See 3 more Smart Citations